2018
DOI: 10.3390/medicina54050072
|View full text |Cite
|
Sign up to set email alerts
|

Lower Airway Virology in Health and Disease—From Invaders to Symbionts

Abstract: Studies of human airway virome are relatively recent and still very limited. Culture-independent microbial techniques showed growing evidence of numerous viral communities in the respiratory microbial ecosystem. The significance of different acute respiratory viruses is already known in the pathogenesis of chronic conditions, such as asthma, cystic fibrosis (CF), or chronic obstructive lung disease (COPD), and their exacerbations. Viral pathogens, such as influenza, metapneumovirus, parainfluenza, respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 77 publications
0
17
0
1
Order By: Relevance
“…In healthy subjects, the similarity of the lung and mouth microbiota varies considerably; it is undetermined whether this variation is persistent over time within subjects or is correlated with clinical phenomena such as esophageal reflux, laryngeal dysfunction, and oral hygiene [6,7]. Metagenomics techniques have demonstrated that in healthy subjects, microorganisms include viruses (virome) [8], fungi (mycome), and bacteria (bacteriome) have an important role in homeostasis [9]. These also participate in host protection against pathogenic microorganisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…In healthy subjects, the similarity of the lung and mouth microbiota varies considerably; it is undetermined whether this variation is persistent over time within subjects or is correlated with clinical phenomena such as esophageal reflux, laryngeal dysfunction, and oral hygiene [6,7]. Metagenomics techniques have demonstrated that in healthy subjects, microorganisms include viruses (virome) [8], fungi (mycome), and bacteria (bacteriome) have an important role in homeostasis [9]. These also participate in host protection against pathogenic microorganisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Virome: The CF lung virome is strongly affected by the mucosal environment and impaired immunity [35]. Common respiratory viruses are found in 60% of CF patients (more than in the general population) and cause greater morbidity than in non-CF subjects [80]. Presence correlates with inflammation, as they interfere with IFN and NF-kappaB pathways, and with bacterial co-infection (including P. aeruginosa), inducing exacerbation and impaired lung function [35,80].…”
Section: Cf Airways Microbiome Ecologymentioning
confidence: 99%
“…Common respiratory viruses are found in 60% of CF patients (more than in the general population) and cause greater morbidity than in non-CF subjects [80]. Presence correlates with inflammation, as they interfere with IFN and NF-kappaB pathways, and with bacterial co-infection (including P. aeruginosa), inducing exacerbation and impaired lung function [35,80]. In addition to eukaryotic viruses, the CF lung microbiome contains phages adapted to this particular environment [35,72,81], and known to impact the microbiome, driving pathogen adaptation and antibiotic resistance [81].…”
Section: Cf Airways Microbiome Ecologymentioning
confidence: 99%
“…Our understanding of the role that the respiratory microbiome (which varies across the varying niches from nose to distal airway) and that of the gut in promoting health and disease within the airways is still at a relatively early stage (105)(106)(107). What seems clear is that our relatively simplistic views of a single organism causing a given acute illness, which is largely based on Kock's postulates formulated more than 120 years ago (108), grossly oversimplifies the complex interactions of individual microorganisms with other members of the microbiome and the host.…”
Section: D) Viral-bacterial Interactionsmentioning
confidence: 99%